Mosaic modularity: an updated perspective and research agenda for the evolution of vascular cambial growth. Issue 4 (14th January 2019) - Tomescu, Alexandru M. F.; Groover, Andrew T.
Summary: Secondary growth from a vascular cambium, present today only in seed plants and isoetalean lycophytes, has a 400‐million‐yr evolutionary history that involves considerably broader taxonomic diversity, most of it hidden in the fossil record. Approaching vascular cambial growth as a complex developmental process, we review data from living plants and fossils that reveal diverse modes of secondary growth. These are consistent with a modular nature of secondary growth, when considered as a tracheophyte‐wide structural feature. This modular perspective identifies putative constituent developmental modules of cambial growth, for which we review developmental anatomy and regulation. Based on these data, we propose a hypothesis that explains the sources of diversity of secondary growth, considered across the entire tracheophyte clade, and opens up new avenues for exploring the origin of secondary growth. In this hypothesis, various modes of secondary growth reflect a mosaic pattern of expression of different developmental–regulatory modules among different lineages. We outline an approach that queries three information systems (living seed plants, living seed‐free plants, and fossils) and integrates data on developmental regulation, anatomy, gene evolution and phylogeny to test the mosaic modularity hypothesis and its implications, and to inform efforts aimed at understanding the evolution of secondary growth.